The structure of economics : a mathematical analysis - Silberberg, Eugene; Suen,Wing. (Chennai : Mcgraw hill education (india) pvt ltd, 2017)
This text combines mathematical economics with microeconomic theory and can be required or recommended as part of a course in graduate microeconomic theory, advanced undergraduate or graduate-level mathematical economics, or any advanced topics course. It also has reference value for international, library, professional and reference markets. This revision addresses significant new topics--the theory of contracts and markets with imperfect information--that have recently become prominent in the microeconomics literature.
1.comparative statics and the paradigm of economics,2.Review of calculus,3.Function of several variables,4.Profit maximization,5.Matricks and determinants,6.Comparative statics the traditional methodology,7.The envelope theorem and duality,8.The derivation of cost function,9.Cost and production function special topics,10.The derivation of consumer demand function,11.Special topics in consumer theory,12.Intertemporal choice,13.Behavior under uncertainty,14.Maximization with inequality and nonnegativity constrains,15.Contracts and incentives.
Includes index.
Keywords: Economics